Self-perceived study on spirituality and productivity among tissue engineering and regenerative medicine researchers in Malaysia - Mohd. Azharuddin, Nur Syamimi; Ahmad Radzi, Muhammad Aa'zamuddin; Hashi, Abdurezak Abdulahi; Sha'ban, Munirah (Kulliyyah of Science,International Islamic University Malaysia, 2017)
There is little to suggest that tissue engineering and regenerative medicine (henceforth TERM) research productivity in Malaysia has been studied from the aspect of spiritual well-being of a researcher. Therefore, this study aimed to assess the spirituality level and productivity among local TERM researchers and to examine the association between both aspects. A structured, cross-sectional questionnaire-based study was conducted online after substantiating a Spirituality Scale (henceforth SS), previously published in one reputable international journal, from the Malaysian context. The SS is a 23-item questionnaire involving self-discovery, relationships, and eco-awareness subscales. The SS underwent few validation procedures which include face validity and in-depth cognitive interview. The SS was then delivered online by using the Google Form application to targeted population. The results were analyzed by using Kruskal Wallis test, Mann-Whitney (U) test and Spearman rank correlation test to analyze (1) the spirituality level of TERM researchers and (2) the relationship between the number or articles related to TERM published by researchers and the spirituality level based on the demographic factors. Most local TERM researchers in Malaysia experienced moderate or high level of spirituality. The overall productivity pattern showed that the total number of articles published by most researchers were between 2 to 5. There was a significant difference between religiosity of an individual and the spirituality level. However, there was no correlation between spirituality and productivity. It can be noted that spirituality level varies according to multiple demographic factors. This present approach in trying to measure the immeasurable dimension of man may be far from its intend